Optimization of Cogent Plant Steam Supply Integrated with PLC Control System in PT. MNA Kuala Tanjung - Dedy Agussyah Putra; Muchsin Harahap (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2022)
Economic dispatch is often used in general to solve the problem of optimizing the fuel consumption of the electric power system, which focuses on developing optimization methods for a generation system. SCADA/PLC is used so that Economic Dispatch can run in real time on a system. In this research, an automation system will be designed that integrates Economic Dispatch into PLC in a generating system of 3 production boilers operating simultaneously (Cogent System) which aims to ensure that the Economic Dispatch system can run in real time. The simulation results show that the Economic Dispatch program on the PLC can run well. In the simulation of a steam load of 76 MT, the optimal value for boiler 1 is 45 MT and for boiler 3 it is 31 MT while in boiler 2 it is 0 MT, with the opportunity to save boiler fuel use by 16.8% and steam production cost can be reduced by 10% from its initial value.